1971
DOI: 10.1002/chin.197144407
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: STICKSTOFFHALTIGE TRITERPENDERIVATE 3. MITT. LUPANDERIVATE 2. MITT.

Abstract: Es werden Versuche unternommen, um die Hydroxylgruppe im Aminolupenol (Ia) durch die Aminogruppe zu ersetzen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In 1958, LUDWICZAK et al. 9 first isolated inotodiol from Inonotus obliquus, which is an unsaturated diol compound with white needle crystal ( Fig. 1a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1958, LUDWICZAK et al. 9 first isolated inotodiol from Inonotus obliquus, which is an unsaturated diol compound with white needle crystal ( Fig. 1a ).…”
Section: Introductionmentioning
confidence: 99%
“…1a ). After 16 years, the chemical structure of inotodiol was determined by chemical degradation and semi-synthesis, and its related physical constants were reported 10 11 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of lupane derivatives with ozone and dimethyldioxirane has been studied [1,2]. It was shown that oxidation of betulin and its acetates by Cr(VI) oxide produced derivatives with keto-and carboxylic groups [3][4][5][6]. Thus, the formation of epimeric C20-acids from the reaction of betulin diacetate (1) with CrO 3 in acetic acid at 70°C was reported [5].…”
mentioning
confidence: 96%